(untitled) (Journal of Entrepreneurship and Business, 2025)
The sustainability and growth of Small and Medium Enterprises (SMEs) are crucial to the economic development every nation, particularly in developing economies like Nigeria, where access to conventional financing is often limited. This study explores the potential of Musharakah, a profit-sharing partnership model rooted in Islamic finance, as a viable funding solution for SMEs in Nigeria. Through a comprehensive analysis of Musharakah’s framework, the study demonstrates how this model aligns with the financial needs and ethical considerations of SMEs within the region’s socio-economic context. By reviewing data collected from SME owners, financial experts, and Islamic finance practitioners, the study assesses the potential impact of Musharakah on SME growth, financial inclusion, and overall economic stability in Nigeria. The findings indicate that Musharakah not only provides a flexible and ethical financing option but also fosters a more collaborative relationship between financial institutions and entrepreneurs.